Immunotherapy in the treatment of non-small cell lung cancer (NSCLC) - analysis of epidemiology and cure - review - Ruszel, Kinga; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2020)
Cancer is the second leading cause of death in Poland. Lung cancer is the leading cause of cancer-related mortality worldwide, with non-small cell lung cancer (NSCLC) accounting for over 85% of all cases. Cancer incidence and mortality trends observed in the world and also Poland for many years, have been the resultants of changes associated with exposure to tobacco smoke carcino-gens (active smoking). Until recently, chemotherapy was the main treatment for NSCLC patients. Currently, thanks to the development of numerous research centers around the world, there are several methods of treating patients, which leads to the extension of cancer patients’ lives and the improvement of their quality. The immune system plays an important role in controlling and eradicating cancer. Immune checkpoint inhibitors (ICPs) have shown clear persistent responses and represent the emergence of a new approach to treating patients with NSCLC. PD-1 inhibitors and PD-L1 inhibitors are a group of checkpoint inhibitors being developed for the treatment of cancer. Programmed cell death 1 (PD-1) is an inhibitory receptor expressed by activated T cells that downmodulates effector functions and limits the generation of immune memory. Immunotherapy with monoclonal antibodies targeting with PD-1 and PD-L1 has become standard of care for an increasing number of indications. However, many patients with metastatic non-small cell lung cancer (mNSCLC) experience disease progression after first- and second- line treatment; therefore more treatment options are needed for these patients. Due to the specific characteristics of cancer immunotherapy and the rapid advances in this field, clinical guidelines for the use of these drugs are needed, including patient selection, response monitoring, careful observation of side effects, and biomarker testing.